The transformation of an agriculture to an industrial-based economy through crowd sourcing in Malaysia - Abdullah, Istikoma; Mastoi, Qurat-ul-ain; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
This paper proposes the concept of transformation an agriculture-based economy to an industrial sector thru crowd sourcing. Malaysia play vital role in change an agriculture-based economy to industries. Other Malaysia’s regional neighbors such as Thailand, Indonesia, Vietnam while still need improvements in many development sectors but focus of this paper to depict value between Malaysia based on the deployment of the (a) Quadruple Helix Model (QHM) is an improvement on the “Triple Helix Model”, which popularized the interaction between industry, academia and government. (b) Whole of Government (WOG) has to facilitate and foster the adoption of these formidable constructs so that innovation can flourish in Malaysia. (c) Network of Mosque (NOM) is focused on creating opportunities to poor and extreme poor on ways to increase their income and break away from the poverty by the small business enterprise such as Azam kerja, Azam Niaga, and Azam Tani. Crowd sourcing plays the important role to support the improving of agriculture by ICT as a tool of one solution to rise the agricultural activity for instance by using mobile, wireless and internet industries like the farmers can prepare for weather related to events, internet function to store large amount of data, mobile phones to disseminate temperature information to remote farmers cheaply especially to prevent crop losses and mitigate effect from natural adversities.